Strategic Industrial Location Selection for SMEs in Indonesia: Integrating Tangible and Intangible Determinants through a Multi-Criteria Decision-Making Framework - Haris Abdulrahman; Amit Kumar Mehar (PT. Mawadaku Sukses Solusindo, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent a critical pillar of economic transformation in developing economies, particularly in emerging markets such as Indonesia. Industrial location selection remains one of the most consequential strategic decisions affecting SME competitiveness, operational efficiency, long-term sustainability, and investment resilience. Existing studies on industrial site selection have predominantly emphasized measurable economic variables while underestimating the strategic significance of intangible determinants such as institutional quality, security stability, regulatory support, and socio-business ecosystems. This study develops an integrated Multi-Criteria Decision-Making (MCDM) framework using the Simple Additive Weighting (SAW) method to evaluate three industrial alternatives in Indonesia: West Java Region, East Java Region, and Central Java Region. The analysis incorporates both tangible and intangible variables to provide a more comprehensive decision architecture for SME industrial location strategy. Primary data were obtained through purposive surveys involving SME owners, industrial consultants, and regional planners, while secondary data were derived from governmental and international institutional reports. The findings demonstrate that Central Java Region achieved the highest composite score due to its balanced cost structure, favorable incentive systems, stronger security conditions, and supportive institutional environment. West Java Region exhibited superior infrastructure and market accessibility but suffered from elevated operational costs and urban complexity. East Java Region provided strong affordability advantages but showed weaknesses in institutional and security dimensions. Sensitivity analysis confirms the robustness of the model under alternative weighting structures and highlights the increasing strategic relevance of intangible variables in industrial planning. The study contributes theoretically by integrating resource-based and institutional perspectives into industrial location analysis and offers practical managerial implications for SME investors, policymakers, and regional development authorities.